Cidadania rompida: a cobertura midiática religiosa durante um processo eleitoral - Osório, Jackeline Gonçalves (2017)
The research in question aims to understand the dynamics of the communication produced by radio stations that carry out religious programming during the electoral period. This methodological approach was based on the analysis of content in order to observe issues such as the guarantee of rights and the interests of religious denominations when carrying out communication procedures.